Factors influencing students' decisions in choosing private institutions of higher education in Malaysia: a structural equation modelling approach - Zain, Osman M.; Jan, Muhammad Tahir; Ibrahim, Andy-Bachtiar (Asian Academy of Management and Penerbit Universiti Sains Malaysia, 2013)
There are almost 500 institutions of private higher education currently in operation in Malaysia, these include colleges, university colleges and universities. These institutions are helpful because they fill the gap caused by limited seating for potential students in government institutions of higher learning. A total sample of 373 students comprising students from secondary schools was used in this study. These students were in the British equivalent O and A levels of education. A questionnaire containing 46 statements was distributed randomly to the respondents during a motivation seminar at their respective schools. The data analysis was conducted using SPSS and AMOS software programme packages for Windows. Factor analysis was performed to extract and decide on the number of factors underlying the measured variables of interest. Structural Equation Modelling (SEM) was then used to examine the variables and the fitness of the proposed model. The results indicate a substantial positive effect of perception and promotion on the students' choice of private institutions for higher education. The results also reveal a significant positive effect of perception on influence and promotion on influence. Therefore, the findings of this study have a substantial effect on private institutions of higher education.